2014
DOI: 10.1016/j.schres.2014.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral approach and avoidance in schizophrenia: An evaluation of motivational profiles

Abstract: Schizophrenia is associated with motivational deficits that interfere with a wide range of goal directed activities. Despite their clinical importance, our current understanding of these motivational impairments is limited. Furthermore, different types of motivational problems are commonly seen among individuals within the broad diagnosis of schizophrenia. The goal of the current study was to examine whether clinically meaningful subgroups could be identified based on approach and avoidance motivational tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
(54 reference statements)
1
15
2
Order By: Relevance
“…One study found high BAS score was related to low negative symptoms measured by PANSS, 26 whereas the other study reported only BIS but not BAS score was positively correlated with expression deficits dimension of the CAINS. 27 The discrepancy may be partly attributed to differences in sample characteristics such as a shorter illness duration in the current study compared to the previous one. 27 Additionally, it is recently suggested that negative symptoms of schizophrenia may involve at least two distinct motivational profiles including high BIS and moderate BAS, and low BIS and BAS, rather than a single motivational dimension solely implicated in these symptoms.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…One study found high BAS score was related to low negative symptoms measured by PANSS, 26 whereas the other study reported only BIS but not BAS score was positively correlated with expression deficits dimension of the CAINS. 27 The discrepancy may be partly attributed to differences in sample characteristics such as a shorter illness duration in the current study compared to the previous one. 27 Additionally, it is recently suggested that negative symptoms of schizophrenia may involve at least two distinct motivational profiles including high BIS and moderate BAS, and low BIS and BAS, rather than a single motivational dimension solely implicated in these symptoms.…”
Section: Discussioncontrasting
confidence: 54%
“… 27 The discrepancy may be partly attributed to differences in sample characteristics such as a shorter illness duration in the current study compared to the previous one. 27 Additionally, it is recently suggested that negative symptoms of schizophrenia may involve at least two distinct motivational profiles including high BIS and moderate BAS, and low BIS and BAS, rather than a single motivational dimension solely implicated in these symptoms. 27 According to this account, a categorical approach rather than considering BIS and BAS as continuous and orthogonal variables may better elucidate motivation systems involved in manifestations of negative symptoms.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We utilized data from 162 participants diagnosed with schizophrenia or schizoaffective disorder (based on the Structured Clinical Interview for DSM-IV ; First et al, 2001) collected as part of a larger study validating a new instrument for the assessment of negative symptoms (Kring et al, 2013); a complete description of the methods has been reported elsewhere (Kring et al, 2013; Reddy et al, 2014). The sample was 57.4% male, with a mean age of 46.84 ( SD = 9.48, Range = 23-65).…”
Section: Methodsmentioning
confidence: 99%
“…Felice Reddy et al investigated asociality in schizophrenia using Gray's model of behavioural approach (i.e., behavioural activation system, BAS, relying on a reward system sensitive to appetitive stimuli and termination of punishment) and behavioural avoidance (i.e., behavioural inhibition system, BIS, sensitive to aversive stimuli, activated by anxiety, novelty, and fear stimuli, and responsible for inhibiting behaviour), and classified subjects according to the presence of negative symptoms and different levels of BIS and BAS scores. Among subjects with elevated negative symptoms, the authors identified two subgroups with different approach/avoidance profiles leading to asociality: one characterized by avoidance tendencies (high inhibition/moderate activation) and another characterized by lack of approach motivation (low inhibition/low activation).…”
Section: Asocialitymentioning
confidence: 99%